Implementation of 14 bits floating point numbers of calculating units for neural network hardware development; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Zoev I. V. Ivan Vladimirovich; Beresnev A. P.; Mytsko E. A. Evgeniy Aleksandrovich; Malchukov A. N. Andrey Nikolaevich (Information technologies in Mechanical Engineering, 2017)
Title screen